Volume 3: Design and Analysis 2009
DOI: 10.1115/pvp2009-77453
|View full text |Cite
|
Sign up to set email alerts
|

On the Buckling of Functionally Graded Cylindrical Shells Under Combined External Pressure and Axial Compression

Abstract: The stability problem of a circular cylindrical shell composed of functionally graded materials with Young’s modulus varying continuously in the thickness direction under combined lateral pressure and axial compression loads is studied in this paper. The formulation is based on the first order shear deformation theory. A load interaction parameter is defined to express the combination of applied axial compression and external pressure. The stability equations are derived by the adjacent equilibrium criterion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It was found that by increasing the ratio of length to radius of the cylindrical panel, critical load always increased. Khazaeinejad et al (2010) analyzed buckling of cylindrical shells made of a functionally graded material under both axial loads and internal pressure by using the first order shear deformation theory. They concluded that by decreasing the power factor of material properties, critical load increased.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that by increasing the ratio of length to radius of the cylindrical panel, critical load always increased. Khazaeinejad et al (2010) analyzed buckling of cylindrical shells made of a functionally graded material under both axial loads and internal pressure by using the first order shear deformation theory. They concluded that by decreasing the power factor of material properties, critical load increased.…”
Section: Introductionmentioning
confidence: 99%